Analisis Gerombol untuk Pengelompokan Program Studi di FMIPA UNSRAT berdasarkan Keadaan Orang Tua - Angelina Monica Gulla; Hanny Andrea Huibert Komalig; Deiby T. Salaki (Sam Ratulangi University, 2023)
This research aims to group study programs in the Faculty of Mathematics and Natural Sciences, Sam Ratulangi University based on the similarity of characteristics from the point of view of the parents of students. The data used in this study is secondary data for 2021, namely new student data obtained from LP3 Sam Ratulangi University Manado. The analysis used is Cluster Analysis. The results of the first cluster analysis contain 2 study programs, namely Chemistry and Physics and the second cluster contains 4 study programs, namely Biology, Pharmacy, Information Systems, and Mathemathics.